Teachers' Read-Aloud Preferences: Perpetuating Sex-Role Stereotypes - Nancy J. Smith; M. Jean Greenlaw; Carolyn Scott (Educational Considerations, 1985)
Just what influence does children's literature, sexist or not, have upon socialization of children?